Stalling chromophore synthesis of the fluorescent protein Venus reveals the molecular basis of the final oxidation step. Issue 22 (9th April 2021) - Auhim, Husam Sabah; Grigorenko, Bella L.; Harris, Tessa K.; Aksakal, Ozan E.; Polyakov, Igor V.; Berry, Colin; Gomes, Gabriel dos Passos; Alabugin, Igor V.; Rizkallah, Pierre J.; Nemukhin, Alexander V.; Jones, D. Dafydd
Abstract : Fluorescent proteins (FPs) have revolutionised the life sciences, but the chromophore maturation mechanism is still not fully understood. Here we photochemically trap maturation at a crucial stage and structurally characterise the intermediate. Abstract : Fluorescent proteins (FPs) have revolutionised the life sciences, but the mechanism of chromophore maturation is still not fully understood. Here we show that incorporation of a photo-responsive non-canonical amino acid within the chromophore stalls maturation of Venus, a yellow FP, at an intermediate stage; a crystal structure indicates the presence of O2 located above a dehydrated enolate form of the imidazolone ring, close to the strictly conserved Gly67 that occupies a twisted conformation. His148 adopts an "open" conformation so forming a channel that allows O2 access to the immature chromophore. Absorbance spectroscopy supported by QM/MM simulations suggests that the first oxidation step involves formation of a hydroperoxyl intermediate in conjunction with dehydrogenation of the methylene bridge. A fully conjugated mature chromophore is formed through release of H2 O2, both in vitro and in vivo . The possibility of interrupting and photochemically restarting chromophore maturation and the mechanistic insights open up new approaches for engineering optically controlled fluorescent proteins.